Hospice Agencies' Hospital Contract Status and Differing Levels of Hospice Care. (May 2015) - Chung, Kyusuk; Richards, Nicole; Burke, Sloane
In response to a 2011 finding that approximately 27% of Medicare-certified hospices do not provide a single day of general inpatient care (GIP), the authors explored the extent to which hospices have contracts with hospitals for GIP. Using the 2007 National Home and Hospice Care Survey, we estimated that 1119 (32%) agencies had no contract with any hospitals in 2007 and half of those with no contract did not have a contract with a skilled nursing facility (SNF) either. As a result, these hospices were unable to provide GIP referrals for those in need of inpatient care for acute pain and symptom management. More importantly, not having a contract with a hospital was just one of the factors influencing GIP provision. In the multivariate logistic model, after controlling for contract status with a hospital and other hospice characteristics, agencies in the second quartile of hospice patient census (12-29 vs 73 or more, adjusted odds ratio = 14.10; 95% confidence interval 4.26-46.62) were independently related to providing only routine home care. These hospices are more likely to rely solely on scatter beds for GIP provision. Given that a significant portion of hospices do not have a contract with a hospital, policy makers need to understand barriers to contracts with a hospital/SNF for GIP and consider a hospice's contract status as one of the standards for hospice certification. In addition, further research is necessary to understand why hospices that do have a contract with a hospital do not make GIP referral.